KEJAHATAN PERDAGANGAN MANUSIA SEBAGAI HUMAN SECURITY ISSUES DI INDONESIA 2005-2009 - Permana Adhinata, Made Bayu (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2012)
The aim of this paper is to understand how the human trafficking is one of the transnational crimes which is an issue in human history. Human trafficking is a new threats of human being in the world and this issue is come up also became concern for state to overcome the problem. This crime is defying human rights and turn the people into a poor worker, slave, commercial sex workers, etc. Indonesia is the country that have problems with this trafficking  because  in  this  country  lie  a  thousand  poor  people which  is  vurnerable  to  be  traded.  Therefore,  Indonesia  make serious efforts to overcome this issue through collaboration with various elements of both state actor and non-state actor.